Regulation of inflammatory response in patients with cutaneous leishmaniasis - Nascimento, Maurício T. (2022)
Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Laboratório de Pesquisa Clínica. Salvador, BA, Brasil / Universidade Federal da Bahia. Salvador, BA, Brasil.